2000
DOI: 10.1097/00005344-200002000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin Improves Endothelial Function in Patients with Coronary Artery Disease

Abstract: Tetrahydrobiopterin (BH4) is an essential cofactor for nitric oxide synthase (NOS) and a scavenger of oxygen-derived free radicals. Decreased availability of BH4 leads, under in vitro conditions, to reduced nitric oxide (NO) production and increased superoxide formation. We studied the effect of exogenous BH4 on endothelial function of angiographically normal vessel segments in patients with coronary artery disease. Nineteen patients with coronary artery disease underwent quantitative coronary angiography with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(86 citation statements)
references
References 24 publications
4
81
0
1
Order By: Relevance
“…12 Acute infusion of BH 4 improved endothelial function in angiographically normalappearing segments of coronary arteries in subjects with coronary artery disease or hypercholesterolaemia. 13,14 A similar improvement was observed in the forearm circulation of diabetics and smokers. [15][16][17] These studies have used either parenteral infusion of BH 4 or a single oral dose, and it has not been shown that chronic oral administration of BH 4 could cause a sustained improvement in endothelial function.…”
Section: Introductionsupporting
confidence: 69%
“…12 Acute infusion of BH 4 improved endothelial function in angiographically normalappearing segments of coronary arteries in subjects with coronary artery disease or hypercholesterolaemia. 13,14 A similar improvement was observed in the forearm circulation of diabetics and smokers. [15][16][17] These studies have used either parenteral infusion of BH 4 or a single oral dose, and it has not been shown that chronic oral administration of BH 4 could cause a sustained improvement in endothelial function.…”
Section: Introductionsupporting
confidence: 69%
“…The coupling/uncoupling of eNOS activity is reported to be regulated by BH4 availability [23,24]. CRP treatment resulted in a significant decrease in intracellular BH4 levels (reduced form) as compared to control cells (Fig 2a).…”
Section: Resultsmentioning
confidence: 90%
“…Various clinical studies have also demonstrated that administration of BH4 improves endothelial dysfunction in conditions characterized by reduced availability of NO and increased production of reactive oxygen species, such as hypercholesterolemia [38], coronary artery disease [24] and smoking [39]. BH4 is synthesized through 2 distinct pathways [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of BH4 improves endothelial function in patients with or without CAD (11,12). In addition, decreased BH4/BH2 ratio, a marker of BH4 oxidation, is also an independent factor of impaired vasorelaxation responses to acetylcholine, suggesting that this factor may exert adverse effects on the endothelial function of the coronary artery.…”
mentioning
confidence: 99%